A review of bus arrival time prediction using artificial intelligence. (3rd April 2022) - Singh, Nisha; Kumar, Kranti
Abstract: Buses are one of the important parts of public transport system. To provide accurate information about bus arrival and departure times at bus stops is one of the main parameters of good quality public transport. Accurate arrival and departure times information is important for a public transport mode since it enhances ridership as well as satisfaction of travelers. With accurate arrival‐time and departure time information, travelers can make informed decisions about their journey. The application of artificial intelligence (AI) based methods/algorithms to predict the bus arrival time (BAT) is reviewed in detail. Systematic survey of existing research conducted by various researchers by applying the different branches of AI has been done. Prediction models have been segregated and are accumulated under respective branches of AI. Thorough discussion is presented to elaborate different branches of AI that have been applied for several aspects of BAT prediction. Research gaps and possible future directions for further research work are summarized. This article is categorized under: Application Areas > Science and Technology Technologies > Artificial Intelligence Technologies > Prediction Abstract : Graphical representation of review on bus arrival time prediction using AI